THE RELATIONSHIP BETWEEN CD4 COUNTS AND BODY MASS INDEX IN CHILDREN WITH HIV IN WANGAYA REGIONAL GENERAL HOSPITAL - Sais, Vira Cendana; Suarca, I Kadek; Bikin Suryawan, I Wayan (E-Jurnal Medika Udayana; Vol 14 No 03 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i3.P02, 2025)
Background : By 2023, 1.37 million children under the age of 15 around the world were infected by HIV. Children with HIV have a high prevalence of stunting, underweight, and wasting associated with low CD4 count. The purpose of the study was to determine the relationship of CD4 counts to body mass index-for-age (BMI-for-age) in children with HIV. Patients and Methods: This study was an analytic cross-sectional study at Wangaya Regional General Hospital in January-September 2024. Inclusion criteria are children who have been diagnosed with HIV, aged 0-18 years, have complete medical record data, including age, gender, weight, height, and CD4 counts. Exclusion criteria were incomplete data and patients with overweight and/or obesity. Data were analyzed using Chi-square test, which was processed with the SPSS program; p value <0.05 was considered significant. Results: The number of respondents was 37 children. The mean age was 138.6 months. The gender was predominantly female (56.8%), 29 children (78.3%) had CD4 counts ?500 cells/mL. The mean body weight was 38.8 kg, and the average height is 139.3 cm. BMI-for-age analysis found that 29 children (78.4%) was well-nourished. Opportunistic infections were experienced by 3 children. Analysis of the relationship between CD4 counts and BMI-for-age of children with HIV stated that there was no relationship between the two variables with a p-value of 0.65. Conclusion: There was no association between CD4 count and BMI-for-age in pediatric patients with HIV. Further research is expected to include a larger number of subjects, more complete data, and a larger area.   Keywords: HIV, pediatric, CD4, body mass index